Fiber-To-The-Home (FTTH) Architecture for Mosul, Iraq - Shibghatullah, A.S.; Mohammed, M.M.; Doheir, M.; Majed, A.N. (International Journal of Human and Technology Interaction (IJHaTI), 2017)
Fiber-To-The-Home (FTTH) is the most promising technology that can offer high bandwidth with more reliability and very high Quality of Service (QoS) comparing with the previous kind of traditional internet connection technologies such as DSL. This technology is based on the optical technology, which use fiber optics that connect the internet service to end-user, which is the subscriber. This work is done to investigate factors and challenges of deploying FTTH technology or a suitable architecture in Iraq. There will be challenges and issues that could be faced while implementing a certain type of FTTH architecture. This research investigated the best solution to provide an internet access to the end-user in Iraq that support higher capacity adaptability due to the increasing number of higher bandwidth access request. Firstly, current studies and works was done in order to explore knowledge about FTTH. Next, factors affecting successful deployment was identified through survey among users in Mosul (one of the main cities in Iraq) in order to generate factors by performing the analysis part based on the collected data to help proposing and choosing the suitable FTTH architecture in the end. The results of this research will be helpful for the government and companies that provide the internet access to the end-users in Iraq to deploy the technology successfully.